Gaya Kepemimpinan Kepala Sekolah dan Kecerdasan Emosional Guru: Peninjauan pada Kinerja Guru - Akhmad Khoerul Anwar; Wresni Pujiyati; Ahmad Dasuki Aly (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhhammadiyah kendari, 2022)
Teacher performance can be measured through its role in the world of education which is undergoing continuous change and is influenced by emotional intelligence and the principal's leadership style. The aim of of this reseacrh are: 1) the influence of the principal's leadership style on teacher performance; 2) the influence of teacher emotional intelligence on teacher performance; and 3) the influence of the principal's leadership style and the teacher's emotional intelligence together on teacher performance. This study applies a quantitative procedure using a causal associative approach. The researcher determined 98 private junior high school teachers in Cikedung sub-district, Indramayu district as the research population, as well as the sample in the study. Based on theoretical assumptions and conclusions of data analysis, it can be concluded that both the principal's leadership style (X1) and the teacher's emotional intelligence (X2) have a positive and significant influence on teacher performance (Y). There is a positive and significant effect of principal's leadership style and teacher's emotional intelligence on teacher performance. The magnitude of the influence of the principal's leadership style and teacher's emotional intelligence on teacher performance is based on the results of calculations in the very strong category.